Effects of Antirejection Drugs on Innate Immune Cells After Kidney Transplantation - Zaza, Gianluigi; Leventhal, Jeremy; Signorini, Lorenzo; Gambaro, Giovanni; Cravedi, Paolo (Frontiers in Immunology, 2019)
Over the last decades, our understanding of adaptive immune responses to solid organ transplantation increased considerably and allowed development of immunosuppressive drugs targeting key alloreactive T cells mechanism. As a result, rates of acute rejection dropped and short-term graft survival improved significantly. However, long-term outcomes are still disappointing. Recently, increasing evidence supports that innate immune responses plays roles in allograft rejection and represents a valuable target to further improve long-term allograft survival. Innate immune cells are activated by molecules with stereotypical motifs produced during injury (i.e., damage-associated molecular patterns DAMPS) or infection (i.e. pathogen-associated molecular patterns PAMPs). Activated innate immune cells can exert direct pro- and anti-inflammatory effects, while also priming adaptive immune responses. These cells are activated after transplantation by multiple stimuli, including ischemia-reperfusion injury, rejection, and infections. Data from animal models of graft rejection, show that inhibition of innate immunity promotes development of tolerance. Therefore, understanding mechanisms of innate immunity is important to improve graft outcomes. This review discusses effects of currently used immunosuppressive agents on innate immune responses in kidney transplantation.